2019
DOI: 10.1007/s13311-019-00726-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Behavioral Effects of Anti-Orexinergic Treatments in a Mouse Model of Huntington's Disease

Abstract: Huntington's disease (HD) is associated with sleep and circadian disturbances in addition to hallmark motor and cognitive impairments. Electrophysiological studies on HD mouse models have revealed an aberrant oscillatory activity at the beta frequency, during sleep, that is associated with HD pathology. Moreover, HD animal models display an abnormal sleep-wake cycle and sleep fragmentation. In this study, we investigated a potential involvement of the orexinergic system dysfunctioning in sleep-wake and circadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…observed that orexin in HD has aberrant effect leads to abnormal sleep pattern, and thus orexin antagonist suvorexant may be of great value in restoring normal sleep and behavioral disturbance in HD. [ 81 ] in addition, despite reduction of orexinergic density in HD, these neurons remain functional and illustrate paradoxical effect, it become more modifiable and affect by serotonine and noradrenaline, and less sensitive to the effect of suprachiasmatic nucleus (the master clock of the brain) causing abnormal biological circadian rhythm. [ 81 82 ]…”
Section: Role Of Orexin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…observed that orexin in HD has aberrant effect leads to abnormal sleep pattern, and thus orexin antagonist suvorexant may be of great value in restoring normal sleep and behavioral disturbance in HD. [ 81 ] in addition, despite reduction of orexinergic density in HD, these neurons remain functional and illustrate paradoxical effect, it become more modifiable and affect by serotonine and noradrenaline, and less sensitive to the effect of suprachiasmatic nucleus (the master clock of the brain) causing abnormal biological circadian rhythm. [ 81 82 ]…”
Section: Role Of Orexin In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Nonetheless, a further study of light-mediated circadian entrainment in transgenic HD mice has demonstrated improved survival rates [ 92 ], and another employing timed feeding as a circadian cue has also reported improved motor outcomes [ 93 ]. The most recent pre-clinical study of sleep therapy in HD, using an orexin antagonist, has also demonstrated benefit to cognitive outcome [ 94 ].…”
Section: Sleep and Circadian Abnormalities In Huntington’s Disease: Evidence To Datementioning
confidence: 99%
“…These changes are also consistently observed in animal models of disease, and are attributed to degeneration of the suprachiasmatic nucleus, hypothalamus and striatum. 60,61 They can also occur early in the condition and are associated with higher levels of cognitive impairment and anxiety. 62 Human post-mortem studies have shown a loss of orexin-releasing neurons in individuals diagnosed with HD, while transgenic HD mouse models suggest that changes to SCN circuitry are central in driving circadian disruption.…”
Section: Sleep Disorders In Huntington's Disease (Hd)mentioning
confidence: 99%
“…62 Human post-mortem studies have shown a loss of orexin-releasing neurons in individuals diagnosed with HD, while transgenic HD mouse models suggest that changes to SCN circuitry are central in driving circadian disruption. 60…”
Section: Sleep Disorders In Huntington's Disease (Hd)mentioning
confidence: 99%